Studi Komparatif Pemikiran Ismail Raji Al-Faruqi dan Syed Muhammad Naquib Al-Attas tentang Islamisasi Ilmu Pengetahuan - Siti Banati Sholiha; Muhammad Riza Fajrul Azhar; Entin Suhartin; Ris'an Rusli; Romli Romli (Penerbit dan Percetakan CV. Picmotiv, 2026)
This study aims to analyze the thoughts of Ismail Raji Al-Faruqi and Syed Muhammad Naquib Al-Attas on the Islamization of knowledge within the context of contemporary Islamic education. The background of this research is based on an epistemological crisis caused by the dominance of a secular and dichotomous Western scientific paradigm. This study employs a qualitative approach using library research, analyzed through a descriptive-comparative method. The findings reveal that both scholars share similarities in rejecting the dichotomy of knowledge and emphasize the importance of the principle of tauhid as the foundation for knowledge development. However, there are differences in their approaches: Al-Faruqi emphasizes the systematic and practical integration of knowledge, while Al-Attas focuses on the purification of the concept of knowledge through the reconstruction of worldview and the inculcation of adab. Thus, their thoughts are complementary and relevant for the development of integrative and character-based Islamic education.